Voltage transfer analysis of sandwich coupled inductors for MEMS planar magnetic sensor - Yunas, Jumril; Majlis, Yeop Burhanuddin; Hamzah, Azrul Azlan; Bais, Badariah; Sulaiman, Nadzril (Springer Berlin / Heidelberg, 2014)
An analysis on voltage transfer characteristic of magnetically coupled sandwich inductor is presented. The aim of the study is to determine the effects of induced voltage characteristics on the gain of the transferred magnetic energy at various coil thicknesses. The induced voltage characteristics play an important factor in determining the efficiency of the magnetic field coupling between two separated coils of MEMS planar magnetic sensors. The output voltage response of the fabricated coupled coil was measured in the frequency range from 10 kHz up to 10 MHz using LeCroy oscilloscope at four-terminal probe station, while the resistance characteristics of the coil were measured using Agilent LCR meter for a various thicknesses of the coil structure. The measured device was fabricated using an optimized surface micromachining process. A maximum voltage gain of −0.72 dB was obtained for coil with 1.4 μm thick metal operating at 3 MHz. The results showed that there is significant dependency of coil structure, operating frequency and material parameter on the gain of the energy transferred from the excitation coil to the sensing coil which affects the sensitivity of the sensor.